2022
DOI: 10.3934/qfe.2022005
|View full text |Cite
|
Sign up to set email alerts
|

FDI Escapism: the effect of home country risks on outbound investment in the global economy

Abstract: <abstract> <p>Over the past few decades, large numbers of literatures in behavior finance have examined firm's internationalization motives, with focused on how host country's risk components affect investment inflow. But the effects of home country risk on investment outflow remain unexamined. Therefore, based on the conceptualization of FDI escapism and the combine frameworks of Dunning's eclectic paradigm and internationalization theory, the objectives of this study are twofold: First, to exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Nevertheless, the joint impact of outward FDI and TOP is positively significant and do not conform to the long run estimates presented in Table 8. 4) are not less than 1 (≥ 1) and within the acceptable range (Roodman, 2009, Osabuohien-Irabor andDrapkin, 2022). This indicates absence of instrument proliferation which weaken both autocorrelation and Hansen tests.…”
Section: Robustness Check Estimatesmentioning
confidence: 82%
“…Nevertheless, the joint impact of outward FDI and TOP is positively significant and do not conform to the long run estimates presented in Table 8. 4) are not less than 1 (≥ 1) and within the acceptable range (Roodman, 2009, Osabuohien-Irabor andDrapkin, 2022). This indicates absence of instrument proliferation which weaken both autocorrelation and Hansen tests.…”
Section: Robustness Check Estimatesmentioning
confidence: 82%
“…However [ 18 ], found that FDI has a destructive effect on the quality of the environment in the MENA economies through increasing economic expansion [ 64 ]. established that the economic growth of Pakistan is attained on the wings of diminishing environmental quality [ 65 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consequently, governments in African countries have prioritized FDI as a significant funding source for sustainable development, evident in their adoption of liberal and market-oriented policies and initiatives such as the African Continental Free Trade Area (AfCFTA) agreement, aimed at attracting FDI. As a result, FDI inflows into the region reached $48 billion in 2018, marking a 13% increase over the previous year, despite the global decline in FDI [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, SOEs in the East appear to lack efficiency compared to private firms and gradually become peripheral in the market-based economy at home. The FDI escapism view (e.g., Kottaridi, Giakoulas, and Manolopoulos, 2019;Osabuohien-Irabor and Drapkin, 2022;Witt and Lewin, 2007) informs us that when the domestic environment is no longer conducive to the company's further development, the company tends to diversify to fields or regions where their capabilities can sustain. Further leveraging policy support and diplomatic information, SOEs from the East are more eager than private enterprises to shift their overcapacity overseas.…”
Section: Space Dimension Contingencymentioning
confidence: 99%